Developing the Creative Competence of Future Educators: Problems and Solutions - Yusupova Firuza Hajiboy qizi (International Journal on Integrated Education, 2026)
This article analyzes the current state of developing the creative competence of future teachers in the higher pedagogical education system, existing problems within the system, and their systemic solutions. The study points out the limitations of traditional teaching methods and substantiates the necessity of integrating art-pedagogical tools to enhance students' creative potential. At the end of the article, theoretical and practical recommendations are proposed to improve the professional and creative training of future educators.